Giving Birth to a Male Specialist Obstetrician According to Perspective of Islamic Law - Husnaini; Zulhamdi; Muhammad Diah (Britain International for Academic Research (BIAR) Publisher, 2019)
Women in giving birth still go to the specialist obstetrician when there is a recommendation from the midwife, or the patient comes directly to the obstetrician, the patient no longer chooses or sorts a male or female obstetrician, in the view of the community as if there are no legal issues. Though the proposition of al-Quran and hadith has ordered us to hold our gaze and preserve the genitals of both men and women, to see the aurat (private parts, those parts of the body that cannot be exposed or should be covered according to Islam) which the same sex is still not allowed, much less in different sex. Especially with regard to giving birth that shows all organs including aurat which is very vital, and also explained by the perspective of fiqh ulema who have very strict rules in seeing aurat, even in the case of medical treatment, especially treatment to the doctor in different sex of patient. Likewise with the results of the plenary session-V which explains male patients are not justified to treated by female medical, and vice versa, moreover women giving birth to a male obstetrician is even more not allowed, this is under normal conditions, as for emergency conditions is allowed but still under very strict requirements. So it can be concluded that Islamic law does not allow giving birth to male obstetricians (in normal conditions), except in emergency situations where there is no other choice or in areas where there are no female obstetricians. The Aceh Ulema Consultative Assembly in the results of the ulema's plenary session on the use of defiled drugs and medical services by different sex in the Islamic perspective. With provisions, if only general treatment that does not lead to seeing vital organs in women is prohibited, much less giving birth which is clearly a male doctor looking openly and transparently and touching vital organs in female patients, then it is very not allowed in Islam, except there is no other choice.